Variable temperature Mössbauer investigation of Co0.1Fe0.9S2 nanoparticles. (1st February 2021) - Hu, Shengli; Chen, Haiwen; Mo, Jiajun; Liu, Min
ABSTRACT: Co0.1 Fe0.9 S2 nanoparticles were synthesized by solvothermal method and studied by Mössbauer spectroscopy in the cooling process. Magnetic phase transition can be testified by Mössbauer investigation. The spectrum recorded at room temperature consists of a simple quadrupole doublet, the values of isomer shift and quadrupole splitting of doublet increase gradually with the decrease of temperature. However, the spectrum consists of a sextet when the temperature drops further to 25 K, indicating that the sample changed from paramagnetism to ferromagnetism. The magnetic field at low temperature is probably super-transferred field from the magnetically ordered cobalt atoms through a super-exchange mechanism.